Enterotoxigenic Bacteroides fragilis: A Possible Etiological Candidate for Bacterially-Induced Colorectal Precancerous and Cancerous Lesions - Samin Zamani; Samin Zamani; Reza Taslimi; Akram Sarabi; Seyedesomaye Jasemi; Leonardo A. Sechi; Mohammad Mehdi Feizabadi; Mohammad Mehdi Feizabadi (Frontiers in Cellular and Infection Microbiology, 2020)
Enterotoxigenic Bacteroides fragilis (ETBF) produces Bacteroides fragilis toxin (BFT), which is associated with acute diarrheal, inflammatory bowel disease, and colorectal cancer (CRC). In experimental models, ETBF has been shown to contribute to colon carcinogenesis. The present study was conducted to investigate mucosal colonization of ETBF in the colon to find a possible association between the presence of ETBF and precancerous and cancerous lesions. The mucosal biopsies of involved sites were obtained from 68 patients with precancerous and cancerous lesions and 52 healthy controls (HC). The samples were cultured on Bacteroides Bile Esculin agar. Then, specific primers were designed to detect B. fragilis and bft gene using quantitative real-time PCR, and the possible links of ETBF with clinicopathological characteristics was evaluated. Also real-time PCR was performed to detect the bft gene subtypes. Bacteroides fragilis was detected in 51% of the patients and 48% of HCs cultures. The 16SrRNA gene was found to be present in 63 and 81% of the patients and HCs' samples, respectively. Moreover, the bft gene was detected in 47 and 3.8% of the patients and HCs, respectively. Also, B. fragilis was significantly more abundant in the patients' samples compared to those of HCs. In the patient group, higher odds ratio (OR) of ETBF was significantly associated with serrated lesions and adenoma with low-grade dysplasia. The bft1 gene was the most prevalent subtype of bft gene, followed by the bft2 gene. This was the first study in Iran to demonstrate increased positivity of ETBF in patients with precancerous and cancerous lesions. In this study, the bft gene was found to be associated with CRC, especially in the patients with precancerous lesions and initial carcinogenic lesions. Moreover, the results suggest that mucosal BFT exposure is common and could be a risk factor and a screening marker for developing CRC.